A simplified technique of esophageal self-expandable metallic stent placement without fluoroscopic and endoscopic guidance for treating esophageal carcinoma - Ratnakar Kini; Sabarinathan Ramanathan; Pugazhendhi Thangavel; Premkumar Karunakaran; Kani Shaik Mohamed; Murali Ananthavadivelu (Turkish Journal of Gastroenterology, 2019)
Background/Aims: Self-expandable metallic stent (SEMS) placement with fluoroscopic guidance is a commonly used technique to relieve obstruction in patients with esophageal carcinoma. However, it has disadvantages such as radiation exposure. SEMS placement with endoscopic guidance also has the disadvantages of causing discomfort to patients as the endoscope and SEMS assembly are simultaneously used and it needs two experts for the procedure to be performed. To overcome these disadvantages, a simplified technique for SEMS placement was developed that does not require fluoroscopic or endoscopic guidance. Our objective was to compare the efficacy and safety of this simplified technique with the conventional SEMS placement method. Materials and Methods: This is a retrospective study including patients with esophageal carcinoma who underwent SEMS placement for the palliation of dysphagia. Results: Sixty-two patients were placed on stents for the palliation for esophageal carcinoma, with 46 patients in the conventional technique group (group A) and 16 in the simplified technique group (group B). The duration of the procedure was considerably lesser in group B than in group A (2 min 53 s vs. 15 min 4 s, p=0.001). The technical success rate achieved in groups A and B were 97.82% and 100%, respectively. SEMS placement required two experts in the conventional technique whereas the simplified technique required only one expert. Conclusion: The advantages of the simplified technique are as follows: technical ease, cost-effectiveness, no exposure to radiation, requirement of minimal manpower, and less time-consuming; these advantages make it the technique day-care procedure. Cite this article as: Kini R, Ramanathan S, Thangavel P, Karunakaran P, Mohamed KS, Ananthavadivelu M. A simplified technique of esophageal self-expandable metallic stent placement without fluoroscopic and endoscopic guidance for treating esophageal carcinoma. Turk J Gastroenterol 2018; 29: 78-84.